2001
DOI: 10.1074/jbc.m103541200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ and Zn2+ Levels Regulate the Alternative Cell Density-dependent Secretion of S100B in Human Glioblastoma Cells

Abstract: In recent years, protein translocation has been implicated as the mechanism that controls assembly of signaling complexes and induction of signaling cascades. Several members of the multifunctional Ca 2؉ -(Zn 2؉ -and Cu 2؉ )-binding S100 proteins appear to translocate upon cellular stimulation, and some are even secreted from cells, exerting extracellular functions. We transfected cells with S100B-green fluorescent fusion proteins and followed the relocation in real time. A small number of cells underwent tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 70 publications
1
62
0
Order By: Relevance
“…In addition, our immunofluorescent analysis showed that S100A4 treatment resulted in the translocation of S100A4 from the cytoplasm into the nucleus in SKOV3 cells. Although S100A4 was first identified as cytoplasmic protein, its translocation between the cytoplasm and the nucleus has been reported in human cells in vitro, such as endothelial cells, (30) fibroblasts, (31) glioblastoma cells, (32) and colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our immunofluorescent analysis showed that S100A4 treatment resulted in the translocation of S100A4 from the cytoplasm into the nucleus in SKOV3 cells. Although S100A4 was first identified as cytoplasmic protein, its translocation between the cytoplasm and the nucleus has been reported in human cells in vitro, such as endothelial cells, (30) fibroblasts, (31) glioblastoma cells, (32) and colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1C shows the sequence coverage obtained for both intact sRAGE ( Figure 1B, arrow a) and the ~25 kDa fragment. Notably, coverage obtained for the V and C1 domains was nearly complete in the 25 kDa band ( Figure 1B, arrow b), ranging from a peptide encoding a region of the N-terminus (23)(24)(25)(26)(27)(28)(29) to a peptide near the C-terminus of C1 (199-216).…”
Section: Stability Of Srage Domainsmentioning
confidence: 99%
“…These EF-hand Ca 2+ -binding proteins are best known as mediators of intracellular Ca 2+ signals, although they are also exported from the cell by a yet unknown mechanism (29). S100 proteins have an exposed hydrophobic binding pocket that mediates protein-protein interactions (30)(31)(32).…”
mentioning
confidence: 99%
“…There are now over twenty S100 proteins widely distributed in human tissue (13)(14)(15), including a large numbers of cancers (16 -18), making it the largest family of EF-hand calcium-binding proteins (19). S100B, a 21.5-kDa symmetric homodimer, is overexpressed in malignant melanoma (18), anaplastic astrocytomas (20), and glio-blastomas (21), and in the case of malignant melanoma, high concentrations of S100B correlate directly with poor prognosis in patients (22). More recently, S100B has gained attention, because it binds directly to the p53 tumor suppressor protein in melanoma (23)(24)(25)(26), reduces p53 protein levels (26,27), and inhibits wild-type p53 functions in malignant melanoma (26 -28).…”
mentioning
confidence: 99%